Preparation method of antirust electronic packaging composite film
By dry composited with aluminum-plated polyester film and anti-rust polyethylene PE film through polyurethane adhesive, the problem of poor anti-rust effect of existing packaging composite films is solved, and a higher anti-rust protection effect is achieved, and stronger protection is provided for the packaging of metal and electromechanical products.
Patent Information
- Application Number
- CN202411944947.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
AI Technical Summary
The existing packaging composite films used in metal and electromechanical products have poor anti-rust effect, which can easily lead to rust damage and affect product quality.
The aluminum-plated polyester film and anti-rust polyethylene PE film are dried-composite with polyurethane adhesive, and are cooked to make anti-rust composite packaging material.
It improves the anti-rust performance of packaging materials, forms high-strength anti-rust packaging protection for integrated circuit boards, electronic instruments, and communication equipment, and significantly improves the anti-rust protection effect of metals and electromechanical products.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of production and processing of packaging composite films, and in particular to a method for preparing a rust-proof electronic packaging composite film. Background Art
[0002] Anti-rust packaging materials are widely used in many fields, such as automobiles, machinery, electronics, aerospace, etc. In the automotive industry, anti-rust packaging materials are used to protect automotive parts from rust. In the machinery industry, anti-rust packaging materials are used to protect the metal surface of mechanical equipment during transportation and storage. In the electronics and aerospace fields, anti-rust packaging materials also play an important role to ensure the stability and reliability of products in harsh environments such as high humidity and high salt spray. They are used to increase the storage time of metal parts of electronic products and overcome the shortcomings of insufficient protection of products by traditional methods.
[0003] Taking the packaging composite film used for metal and electromechanical products in processing, warehousing, maritime transportation and external trade as an example, the anti-rust effect of the above-mentioned packaging composite film for metal and electromechanical products is poor, which can easily cause rust damage to metal and electromechanical products and affect product quality. Therefore, a preparation method of anti-rust electronic packaging composite film is proposed to solve the above problems. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a rust-proof electronic packaging composite film, which is used to solve the problem that the above-mentioned packaging composite film for metal and electromechanical products has poor rust-proof effect, easily causes rust damage to metal and electromechanical products, and affects product quality.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing a rust-proof electronic packaging composite film, wherein the preparation materials include an aluminized polyester film, a polyurethane adhesive and a rust-proof polyethylene PE film, and the preparation method includes the following steps:
[0007] S1. Preparation of aluminized polyester film:
[0008] (1) Preparation of biaxially oriented polyester film: pre-drying the PET resin slices to prevent hydrolysis, then extruding an amorphous thick sheet through a T-die at 280°C in an extruder, quenching the thick sheet through a cooling drum or a cooling liquid, and then biaxially stretching the thick sheet, wherein the longitudinal stretching is to preheat the thick sheet to 86-87°C and stretch it 3 times along the plane extension direction of the thick sheet at this temperature, the transverse stretching preheating temperature is 98-100°C, the stretching temperature is 100-120°C, and the stretching ratio is 2.5-4.0. The film after longitudinal and transverse stretching is heat-set, wherein the heat-setting temperature is 230-240°C, and a biaxially oriented polyester film with good thermal stability is prepared;
[0009] (2) Preparation of aluminum nitride coating: Place the biaxially oriented polyester film into a coating chamber containing metallic chromium, maintain a vacuum degree of less than 1.5×10-3Pa, and heat to 135 degrees Celsius, continuously introduce nitrogen and argon into the device, set the sputtering power to 12KW, and continue magnetron sputtering for 5 minutes. Nitrogen reacts with the sputtered chromium atoms to form a nitride layer, which is uniformly deposited on the surface of the biaxially oriented polyester film;
[0010] (3) Aluminum evaporation: The polyester film is rolled into a tube, and before evaporation, the tube-shaped polyester film is transported and moved by an external unwinding device and a winding device, and the polyester film is transported and moved inside a vacuum evaporation machine. A vacuum pump installed inside the vacuum evaporation machine performs vacuum treatment so that the vacuum degree reaches 1.3×10-2 to 1.3×10-3Pa, and the evaporation boat is heated to 1300°C to 1400°C, and then aluminum wire with a purity of 99.9% is continuously fed to the evaporation boat. , adjust the polyester film unwinding speed, polyester film winding speed, aluminum wire conveying speed and aluminum wire evaporation amount, open the cooling source, make the aluminum wire melt and evaporate continuously on the evaporation boat, so as to form a bright aluminum layer on the surface of the nitride layer of the polyester film after cooling, the thickness of the aluminum layer is 50-150nm, the width of the aluminum film is 800mm-2000mm, and the aluminum-plated polyester film is formed, and then the laser thickness measurement is carried out. After the aluminum layer thickness inspection is qualified, it is flattened and rolled;
[0011] S2. Preparation of rust-proof polyethylene PE film: wherein the rust-proof polyethylene PE film is processed by a three-layer co-extrusion film blowing machine, wherein the raw material of the first layer is a mixture of 70% medium-density metallocene and 30% low-density metallocene, the raw material of the second layer is a mixture of 60-70% linear low-density polyethylene, 15-25% metallocene polyethylene, and 5-15% mixed titanium dioxide masterbatch, and the third layer is a mixture of 20-30% low-density polyethylene, 25-40% metallocene polyethylene, 40-50% linear low-density polyethylene, and 2-5% rust-proof masterbatch:
[0012] The working process of the three-layer co-extrusion film blowing machine in the production of rust-proof polyethylene PE film is as follows: first, three layers of different types of plastic raw materials are placed in their respective extruders, heated and melted by their respective extruders, and then formed into a melt through the die head. The melt then enters the blowing device. During this process, air is injected into the melt and quickly blown up to form a film. The film then enters the cooling system to quickly cool and harden. Finally, the traction and winding device tractions and winds up the hardened film;
[0013] S3, dry composite process:
[0014] (1) Pretreatment: The wide film roll obtained in the above steps S1 and S2 is cut into narrow film rolls of required specifications, wherein an appropriate margin should be set during cutting, and the width of the film roll obtained by cutting is 15-25 mm larger than the required width of the finished product;
[0015] (2) Composite treatment:
[0016] A1. First, install the aluminum-plated polyester film base film roll on the motor reel, place the film according to the direction specified by the equipment, and install the rust-proof polyethylene PE film base film roll, then lift a group of rollers of the rubber roller to make the base film roll not contact with the rubber roller;
[0017] A2. Add polyurethane adhesive to the adhesive disc, turn on the oven heater, start the auxiliary drive motor, adjust the pressure between the rubber roller and the anilox roller, and coat the rubber roller with a thin and even layer of polyurethane adhesive. When the oven temperature reaches the required temperature, start the cooling equipment and heat dissipation equipment to maintain the oven temperature, turn off the auxiliary drive motor, lower the roller on the rubber roller, press the aluminized polyester film substrate against the rubber roller, and laminate the rust-proof polyethylene PE film substrate with the aluminized polyester film substrate through the polyurethane adhesive;
[0018] S4, aging treatment:
[0019] The film compounded in the above step S3 is placed in a aging chamber to allow the main agent and curing agent in the polyurethane adhesive to undergo a cross-linking reaction and interact with the surface of the aluminum-plated polyester film substrate and the anti-rust polyethylene PE film substrate, so that the main agent and curing agent in the polyurethane adhesive can fully react within a certain period of time to achieve the best composite strength, while removing the residual solvent with a low boiling point in the polyurethane adhesive. Finally, the film is made into a packaging film bag that meets the size requirements of the product through a bag-making equipment for use.
[0020] Preferably, the anti-rust masterbatch in step S2 is a mixture of sodium molybdate and benzotriazole in equal mass proportions, which is used as the anti-rust additive in step S2.
[0021] Preferably, the drying tunnel heater used in step A2 is a three-stage heating structure, wherein the front end temperature of the drying tunnel is 50-60°C, the middle end temperature is 60-70°C, the rear end temperature is 70-80°C, and the coating amount of the polyurethane adhesive is 2.5-3.5 g / ㎡.
[0022] Preferably, in step S4, the temperature inside the curing chamber is maintained at 45-50° C., a ventilation and exhaust pipe structure is provided inside the curing chamber, and the curing time is 24-36 hours.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] In the present invention, the structure of the rust-proof electronic packaging composite film is that the packaging material is made of aluminum-plated polyester film through dry compounding, and is compounded with rust-proof polyethylene PE film using polyurethane adhesive, and is made into rust-proof composite packaging material after aging. The rust-proof composite packaging material has performance indicators such as barrier, rust prevention, high strength, and weather resistance. Through the above-mentioned arrangement, high-strength rust-proof packaging protection for integrated circuit boards, electronic instruments, and communication equipment is formed. Compared with the currently used electronic packaging composite film, it is used for the packaging treatment of metals and electromechanical products, is not easy to cause rust damage to metals and electromechanical products, and has a higher rust-proof protection effect. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] The present invention provides a technical solution:
[0027] A method for preparing a rust-proof electronic packaging composite film, wherein the preparation materials include an aluminized polyester film, a polyurethane adhesive and a rust-proof polyethylene PE film, and the preparation method includes the following steps:
[0028] S1. Preparation of aluminized polyester film:
[0029] (1) Preparation of biaxially oriented polyester film: pre-drying the PET resin slices to prevent hydrolysis, then extruding an amorphous thick sheet through a T-die at 280°C in an extruder, quenching the thick sheet through a cooling drum or a cooling liquid, and then biaxially stretching the thick sheet, wherein the longitudinal stretching is to preheat the thick sheet to 86-87°C and stretch it 3 times along the plane extension direction of the thick sheet at this temperature, the transverse stretching preheating temperature is 98-100°C, the stretching temperature is 100-120°C, and the stretching ratio is 2.5-4.0. The film after longitudinal and transverse stretching is heat-set, wherein the heat-setting temperature is 230-240°C, and a biaxially oriented polyester film with good thermal stability is prepared;
[0030] (2) Preparation of aluminum nitride coating: Place the biaxially oriented polyester film into a coating chamber containing metallic chromium, maintain a vacuum degree of less than 1.5×10-3Pa, and heat to 135 degrees Celsius, continuously introduce nitrogen and argon into the device, set the sputtering power to 12KW, and continue magnetron sputtering for 5 minutes. Nitrogen reacts with the sputtered chromium atoms to form a nitride layer, which is uniformly deposited on the surface of the biaxially oriented polyester film;
[0031] (3) Aluminum evaporation: The polyester film is rolled into a tube, and before evaporation, the tube-shaped polyester film is transported and moved by an external unwinding device and a winding device, and the polyester film is transported and moved inside a vacuum evaporation machine. A vacuum pump installed inside the vacuum evaporation machine performs vacuum treatment so that the vacuum degree reaches 1.3×10-2 to 1.3×10-3Pa, and the evaporation boat is heated to 1300°C to 1400°C, and then aluminum wire with a purity of 99.9% is continuously fed to the evaporation boat. , adjust the polyester film unwinding speed, polyester film winding speed, aluminum wire conveying speed and aluminum wire evaporation amount, open the cooling source, make the aluminum wire melt and evaporate continuously on the evaporation boat, so as to form a bright aluminum layer on the surface of the nitride layer of the polyester film after cooling, the thickness of the aluminum layer is 50-150nm, the width of the aluminum film is 800mm-2000mm, and the aluminum-plated polyester film is formed, and then the laser thickness measurement is carried out. After the aluminum layer thickness inspection is qualified, it is flattened and rolled;
[0032] S2. Preparation of rust-proof polyethylene PE film: wherein the rust-proof polyethylene PE film is processed by a three-layer co-extrusion film blowing machine, wherein the raw material of the first layer is a mixture of 70% medium-density metallocene and 30% low-density metallocene, the raw material of the second layer is a mixture of 60-70% linear low-density polyethylene, 15-25% metallocene polyethylene, and 5-15% mixed titanium dioxide masterbatch, and the third layer is a mixture of 20-30% low-density polyethylene, 25-40% metallocene polyethylene, 40-50% linear low-density polyethylene, and 2-5% rust-proof masterbatch:
[0033] The working process of the three-layer co-extrusion film blowing machine in the production of rust-proof polyethylene PE film is as follows: first, three layers of different types of plastic raw materials are placed in their respective extruders, heated and melted by their respective extruders, and then formed into a melt through the die head. The melt then enters the blowing device. During this process, air is injected into the melt and quickly blown up to form a film. The film then enters the cooling system to quickly cool and harden. Finally, the traction and winding device tractions and winds up the hardened film;
[0034] S3, dry composite process:
[0035] (1) Pretreatment: The wide film roll obtained in the above steps S1 and S2 is cut into narrow film rolls of required specifications, wherein an appropriate margin should be set during cutting, and the width of the film roll obtained by cutting is 15-25 mm larger than the required width of the finished product;
[0036] (2) Composite treatment:
[0037] A1. First, install the aluminum-plated polyester film base film roll on the motor reel, place the film according to the direction specified by the equipment, and install the rust-proof polyethylene PE film base film roll, then lift a group of rollers of the rubber roller to make the base film roll not contact with the rubber roller;
[0038] A2. Add polyurethane adhesive to the adhesive disc, turn on the oven heater, start the auxiliary drive motor, adjust the pressure between the rubber roller and the anilox roller, and coat the rubber roller with a thin and even layer of polyurethane adhesive. When the oven temperature reaches the required temperature, start the cooling equipment and heat dissipation equipment to maintain the oven temperature, turn off the auxiliary drive motor, lower the roller on the rubber roller, press the aluminized polyester film substrate against the rubber roller, and laminate the rust-proof polyethylene PE film substrate with the aluminized polyester film substrate through the polyurethane adhesive;
[0039] S4, aging treatment:
[0040] The film compounded in the above step S3 is placed in a aging chamber to allow the main agent and curing agent in the polyurethane adhesive to undergo a cross-linking reaction and interact with the surface of the aluminum-plated polyester film substrate and the anti-rust polyethylene PE film substrate, so that the main agent and curing agent in the polyurethane adhesive can fully react within a certain period of time to achieve the best composite strength, while removing the residual solvent with a low boiling point in the polyurethane adhesive. Finally, the film is made into a packaging film bag that meets the size requirements of the product through a bag-making equipment for use.
[0041] In step S2, the anti-rust masterbatch is a mixture of sodium molybdate and benzotriazole in equal mass proportions, which is used as the anti-rust additive in step S2. Through the above settings, by adding the anti-rust masterbatch, it is convenient to perform anti-rust modification on the polyethylene PE film made by the three-layer co-extrusion film blowing machine.
[0042] The drying oven heater used in step A2 is a three-stage heating structure, in which the front end temperature of the drying oven is 50-60°C, the middle end temperature is 60-70°C, and the rear end temperature is 70-80°C. The coating amount of the polyurethane adhesive is 2.5-3.5g / ㎡. Through the above settings, a three-stage step-by-step heating treatment is adopted, which is conducive to the compounding of the rust-proof polyethylene PE film and the aluminum-plated polyester film through the curing and drying treatment of the polyurethane adhesive.
[0043] In step S4, the temperature inside the aging chamber is maintained at 45-50° C., a ventilation and exhaust pipe structure is provided inside the aging chamber, and the aging time is 24-36 hours. Through the above settings, the polyurethane adhesive is aged, which is beneficial to improve the bonding strength between the anti-rust polyethylene PE film and the aluminized polyester film.
[0044] Working process: The rust-proof electronic packaging composite film prepared by the present invention is mainly used for packaging of electronic products, auto parts and the like.
[0045] The structure of the rust-proof electronic packaging composite film is that the packaging material is made of aluminized polyester film through dry compounding, and is compounded with rust-proof polyethylene PE film using polyurethane adhesive. After aging, it is made into rust-proof composite packaging material, which has barrier, rust-proof, high-strength, weather-resistant and other performance indicators, forming high-strength rust-proof packaging protection for integrated circuit boards, electronic instruments, and communication equipment. Compared with the currently used electronic packaging composite film, it is used for the packaging of metal and electromechanical products, is not easy to cause rust damage to metal and electromechanical products, and has a higher rust-proof protection effect. It is particularly suitable for metal and electromechanical products in processing, warehousing, maritime transportation, and foreign businessmen's high-quality rust-proof requirements for import and export products.
[0046] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a rust-proof electronic packaging composite film, characterized in that: The preparation materials include aluminized polyester film, polyurethane adhesive and anti-rust polyethylene PE film; The preparation method comprises the following steps: S1. Preparation of aluminized polyester film: (1) Preparation of biaxially oriented polyester film: pre-drying the PET resin slices to prevent hydrolysis, then extruding an amorphous thick sheet through a T-die at 280°C in an extruder, quenching the thick sheet through a cooling drum or a cooling liquid, and then biaxially stretching the thick sheet, wherein the longitudinal stretching is to preheat the thick sheet to 86-87°C and stretch it 3 times along the plane extension direction of the thick sheet at this temperature, the transverse stretching preheating temperature is 98-100°C, the stretching temperature is 100-120°C, and the stretching ratio is 2.5-4.
0. The film after longitudinal and transverse stretching is heat-set, wherein the heat-setting temperature is 230-240°C, and a biaxially oriented polyester film with good thermal stability is prepared; (2) Preparation of aluminum nitride coating: The biaxially oriented polyester film is placed in a coating chamber containing metallic chromium and the vacuum is maintained at less than 1.5×10 -3 Pa, and heated to 135 degrees Celsius, nitrogen and argon were continuously introduced into the device, the sputtering power was set to 12KW, and magnetron sputtering was continued for 5 minutes. Nitrogen reacted with the sputtered chromium atoms to form a nitride layer, which was evenly deposited on the surface of the biaxially oriented polyester film; (3) Aluminum evaporation: The polyester film is rolled into a tube, and before evaporation, the tube-shaped polyester film is transported and moved by an external unwinding device and a winding device, and the polyester film is transported and moved inside a vacuum evaporation machine, and a vacuum pump provided inside the vacuum evaporation machine is used for vacuuming, so that the vacuum degree reaches 1.3×10 -2 ~1.3×10 -3 Pa, the evaporation boat is heated to 1300℃~1400℃, and then the aluminum wire with a purity of 99.9% is continuously fed to the evaporation boat, the polyester film unwinding speed, the polyester film winding speed, the aluminum wire feeding speed and the aluminum wire evaporation amount are adjusted, and the cooling source is turned on to make the aluminum wire melt and evaporate continuously on the evaporation boat, so that a bright aluminum layer is formed on the surface of the nitride layer of the polyester film after cooling, and the thickness of the aluminum layer is 50~150nm, and the width of the aluminum film is 800mm~2000mm, so as to form an aluminum-plated polyester film, and then the laser thickness measurement is carried out, and after the aluminum layer thickness inspection is qualified, it is flattened and rolled; S2. Preparation of rust-proof polyethylene PE film: wherein the rust-proof polyethylene PE film is processed by a three-layer co-extrusion film blowing machine, wherein the raw material of the first layer is a mixture of 70% medium-density metallocene and 30% low-density metallocene, the raw material of the second layer is a mixture of 60-70% linear low-density polyethylene, 15-25% metallocene polyethylene, and 5-15% mixed titanium dioxide masterbatch, and the third layer is a mixture of 20-30% low-density polyethylene, 25-40% metallocene polyethylene, 40-50% linear low-density polyethylene, and 2-5% rust-proof masterbatch: The working process of the three-layer co-extrusion film blowing machine in the production of rust-proof polyethylene PE film is as follows: first, three layers of different types of plastic raw materials are placed in their respective extruders, heated and melted by their respective extruders, and then formed into a melt through the die head. The melt then enters the blowing device. During this process, air is injected into the melt and quickly blown up to form a film. The film then enters the cooling system to quickly cool and harden. Finally, the traction and winding device tractions and winds up the hardened film; S3, dry composite process: (1) Pretreatment: The wide film roll obtained in the above steps S1 and S2 is cut into narrow film rolls of required specifications, wherein an appropriate margin should be set during cutting, and the width of the film roll obtained by cutting is 15-25 mm larger than the required width of the finished product; (2) Composite treatment: A1. First, install the aluminum-plated polyester film base film roll on the motor reel, place the film according to the direction specified by the equipment, and install the rust-proof polyethylene PE film base film roll, then lift a group of rollers of the rubber roller to make the base film roll not contact with the rubber roller; A2. Add polyurethane adhesive to the adhesive disc, turn on the oven heater, start the auxiliary drive motor, adjust the pressure between the rubber roller and the anilox roller, and coat the rubber roller with a thin and even layer of polyurethane adhesive. When the oven temperature reaches the required temperature, start the cooling equipment and heat dissipation equipment to maintain the oven temperature, turn off the auxiliary drive motor, lower the roller on the rubber roller, press the aluminized polyester film substrate against the rubber roller, and laminate the rust-proof polyethylene PE film substrate with the aluminized polyester film substrate through the polyurethane adhesive; S4, aging treatment: The film compounded in the above step S3 is placed in a aging chamber to allow the main agent and curing agent in the polyurethane adhesive to undergo a cross-linking reaction and interact with the surface of the aluminum-plated polyester film substrate and the anti-rust polyethylene PE film substrate, so that the main agent and curing agent in the polyurethane adhesive can fully react within a certain period of time to achieve the best composite strength, while removing the residual solvent with a low boiling point in the polyurethane adhesive. Finally, the film is made into a packaging film bag that meets the size requirements of the product through a bag-making equipment for use.
2. The method for preparing a rust-proof electronic packaging composite film according to claim 1, characterized in that: The anti-rust masterbatch in step S2 is a mixture of sodium molybdate and benzotriazole in equal weight proportions, which is used as an anti-rust additive in step S2.
3. The method for preparing a rust-proof electronic packaging composite film according to claim 1, characterized in that: The drying oven heater used in step A2 is a three-stage heating structure, in which the front end temperature of the drying oven is 50-60°C, the middle end temperature is 60-70°C, and the rear end temperature is 70-80°C. The coating amount of the polyurethane adhesive is 2.5-3.5g / ㎡.
4. The method for preparing a rust-proof electronic packaging composite film according to claim 1, characterized in that: In step S4, the temperature inside the curing chamber is maintained at 45-50°C, a ventilation and exhaust pipe structure is provided inside the curing chamber, and the curing time is 24-36 hours.